Aditivos alimentares: impactos na saúde humana e o desafio da indústria alimentícia frente ao movimento clean label - Bazana, Natália Diniz (Universidade Federal de São Carlos, 2024)
Food additives are widely used by the industry to extend product shelf life, enhance sensory characteristics, and ensure food safety. Among the main additives used in food are preservatives, colorants, antioxidants, and acidity regulators, which play essential roles in preserving product quality. However, the prolonged use of artificial additives has been associated with health risks, such as allergic reactions, toxicity, and carcinogenic effects, especially when consumed in quantities exceeding recommended limits. Thus, the objective of this study was to conduct a literature review addressing the importance of food additives, focusing on preservatives and the impacts of their prolonged consumption, as well as the clean label trend aimed at reducing their use in foods. The bibliographic review, based on studies on the subject from the last five years and current regulations, reveals that the food industry has increasingly sought natural and safe alternatives without compromising preservative effectiveness due to the relationship of these compounds with product shelf life. Furthermore, the clean label trend, which aims to reduce the use of artificial additives and replace them with natural ingredients, also promotes greater transparency in labeling, enabling consumers to make more informed choices. Although natural alternatives offer health and sustainability benefits, they face challenges such as lower efficacy and higher costs. In conclusion, due to the significant growth potential of the natural and safe food market, additional studies are needed to evaluate the benefits of these alternatives, develop new formulations, and improve production processes.
Food additives: impacts on human health and the food industry’s challenge in the face of the clean label movement
Keywords: Conservantes; Ingredientes naturais; Novas tecnologias; Segurança alimentar; Preservatives; Natural ingredients; New technologies; Food safety; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS